COMPARISON OF BUSINESS PROCESS MODELING STANDARDS (International Journal of Engineering Sciences & Management Research, 2014)
The article emphasizes the important role of business process modeling in business management and explores the standards used formodeling of business processes. It presents trends for the use of these standards over the years. The main building elements of EPCand BPMN standards are presented and their main advantages and disadvantages of are discussed. A comparative analysis of the twostandards on six major indicators is made. The results of the analysis show that none of the standards is superior to the other in allcases and that the most appropriate is to choose standard for modeling for each specific subject area.